Analysis of Students' Perceptions of Online Learning in PAI Subjects and Class IX Characteristics at SMP Sejahtera Kendari Academic Year 2020/2021 - Marwan (Jurnal Multidisiplin Madani, 2022)
The application of online learning has utilized various digital media platforms to face challenges in the world of education during the Covid-19 pandemic. This study aims to determine students' perceptions of online learning in Islamic Islamic Education and Characteristics Class IX subjects at Sejahtera Kendari Middle School. This type of research is a mixed method, which is action-oriented by using both quantitative and qualitative methods in the process of implementing the same research. The sample of this research was class IX students at SMP Sejahtera Kendari where the sample was taken using purposive sampling. The data collection method used was a questionnaire on a Likert item scale and interviews. The questionnaire was used to find out students' perceptions of online learning in PAI and Moral Education subjects. Meanwhile, the results of the interviews were to find out the factors that influence online learning on the learning outcomes of Class IX students at SMP Sejahtera Kendari. In addition, researchers used data analysis techniques in the form of descriptive statistics through SPSS and Miles & Huberman's theory. The results of the study showed that the majority of students showed a positive perception of online learning in PAI subjects with the 'S' and SS' categories of 75%. In addition, the factors that influence online learning based on the results of interviews are (1) network constraints that do not support, (2) excessive assignments, and (3) lack of understanding of learning material